Multinucleated histiocytes in esophageal squamous mucosa secondary to gastroesophageal reflux disease in a patient with esophageal stricture. Issue 8 (26th February 2015) - Davis‐Yadley, A. H.; Keshishian, J.; Champeaux, A.; Richter, J. E.
Summary: We present a novel finding of multinucleated histiocytes associated with acute and chronic inflammation secondary to gastroesophageal reflux in a patient with a history of esophageal stricture, representing the first documented case after a review of the literature. Multinucleated squamous cells, while rare, are a more common finding in association with reactive and inflammatory conditions and have been reported in other areas of the body, such as the vulva, skin, and colon. Esophageal involvement with multinucleated epithelial giant cells appears to be a much less frequently encountered occurrence with only one previous report in the literature. We add to this series an interesting case of esophageal multinucleated giant cells that are histiocytes rather than epithelial cells, supported with positive CD68 immunohistochemical staining. Our patient had severe esophageal dysphagia with stricture with history of food impaction, requiring several dilation sessions to achieve an esophageal luminal diameter of 17 mm. There was marked clinical and endoscopic improvement with proton pump inhibitor and endoscopic therapy. The multinucleated mucosal histiocytes at the time of biopsy were likely due to reactive changes from chronic injury due to food stasis and reflux.